2020
DOI: 10.1038/s41557-020-0465-9
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein aggregation nucleates through liquid–liquid phase separation

Abstract: doi: bioRxiv preprint their components rapidly with the surrounding medium (Hyman et al., 2014;. Most of the liquid condensates possess common characteristics, which include their formation mechanism as well as their physical properties. For instance, multivalent proteins or nucleic acids associate through weak intermolecular interactions and reach a solubility limit to form liquid condensates (Banani et al., 2017;. These condensates are highly mobile, spherical, but get deformed on physical contact, fuse and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
858
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(924 citation statements)
references
References 127 publications
(144 reference statements)
60
858
4
2
Order By: Relevance
“…This phenomenon has been observed for FUS and TDP-43 in ALS [38,39] and more recently also for tau in Alzheimer's disease [40][41][42]. Our results show that a-synuclein can undergo a similar process by forming a dense liquid droplet state, which matures into a gel-like state rich in amyloid structure, consistently with very recent results [43].…”
supporting
confidence: 91%
“…This phenomenon has been observed for FUS and TDP-43 in ALS [38,39] and more recently also for tau in Alzheimer's disease [40][41][42]. Our results show that a-synuclein can undergo a similar process by forming a dense liquid droplet state, which matures into a gel-like state rich in amyloid structure, consistently with very recent results [43].…”
supporting
confidence: 91%
“…Additionally, the study of the τ and correlation time of the pathogenic alpha-synuclein mutants, A30P and A53T, showed that they had distinct types of binding sites, which was in concordance with the difference in fibril morphology [ 120 ]. Additionally, the anisotropy decay profiles of fluorescein labelled-alpha synuclein have recently been used to study its liquid–liquid phase separation into droplets, an event that occurs before protein fibrillation [ 121 ].…”
Section: Fluorescence Spectroscopy Is a Versatile Tool For Evaluatmentioning
confidence: 99%
“…Indeed, recent experimental evidences suggest a role of these protein droplets on the in vivo aggregation of these amyloidogenic proteins and the induction of pathology 66 . Very recently, it has been reported that αS droplet formation by LLPS precedes its aggregation in cellular 67 and animal models 68 and the liquid-to-solid transition of αS droplets has been recapitulated in vitro.…”
Section: Antiparallel -Sheet Aggregates Represent the Most Stable Stmentioning
confidence: 99%